The effect of brand sustainability initiatives in South Africa on the buying behaviour and brand loyalty of Durban consumers.” - Rajoo, Shivar (The IIE, 2019)
Sustainability has now become a key driver of both businesses and consumer lifestyles. Harvard Business Review posits that as the expectations on corporate responsibility increases and as transparency becomes more prevalent due to the demand by consumers supporting brands who engage in both ethical and sustainable practices, there has been a shift in the consumer mindset from one that is focused on solely a product to one that can aid in building a sustainable future. Companies are therefore recognizing the need to act on sustainability where professional communications and good intentions are no longer enough to satisfy consumers (Whelan, 2016). This study used data in the form of qualitative data to incorporate structured interviews, unstructured interviews, a survey and ethnography into understanding the extent towards which South African sustainability initiatives influence consumer buying behaviour. Primary and secondary research concluded that a majority percentage of South African consumers are brand loyal to, and support brands engaging in sustainable initiatives parallel to their own beliefs and values. However, should brands engage in unethical or unsustainable practices, South African consumers are not hesitant to switch to alternative or competitor brands.
Keywords: Brand loyalty; Sustainability; Consumer behaviour; Brand value